Discursive features of animal agriculture advocates - Coombes, Stephanie (Kansas State University, 2016)
The general public is more generationally and geographically removed from agricultural production today than ever before, yet as influential as ever with regards to its ability to impact the operating conditions of the animal agriculture industry. To date, the agriculture industry has focused research and extension on how to educate and persuade the public in order to gain support for its practices and policies. Little work has investigated how the language choices of those communicating about agriculture may be functioning to position themselves and other participants with regards to authority and credibility, and how this affects their communication and the industry as a whole. This study sought to develop an understanding as to how three key groups in the animal agriculture conversation (experts, professional communicators, and agricultural advocates) use discourse and language to position themselves and other participants, their explanations of opposition to animal agriculture, and their ideas about how to best present and justify their arguments to the wider public. In addition to this, the study also sought to understand what power structures and dynamics exist within the conversation. Semi-structured interviews were conducted to collect data for a critical discourse analysis. The discursive practices of the participants functioned to ultimately undermine and delegitimize the role of the public and individuals and groups opposed to animal agriculture, as well as position the industry and its constituents as the only authoritative and credible voices in the animal agriculture conversation. This is likely to be prohibitive to achieving the goals of agricultural communication activities. Those communicating on behalf of the animal agriculture industry should become more aware of how their beliefs, values, and ideologies impact the discourse from which they are operating, as well as how their communication is functioning. This research was undertaken from a critical inquiry perspective, shedding light on some of the power structures inherent between the animal agriculture industry and the general public. Others undertaking agricultural sociology and related research should consider doing so integrating a similar theoretical perspective to continually challenge the assumptions and conditions under which the industry operates.
Keywords: Discourse analysis; Animal agriculture; Critical inquiry